Ulcerative Colitis Patients Continue to Improve Over the First Six Months of Vedolizumab Treatment: 12-Month Clinical and Mucosal Healing Effectiveness. Issue 2 (22nd November 2018) - Zezos, Petros; Kabakchiev, Boyko; Weizman, Adam V; Nguyen, Geoffrey C; Narula, Neeraj; Croitoru, Kenneth; Steinhart, A Hillary; Silverberg, Mark S
Abstract: Background: Vedolizumab (VDZ) is a humanized monoclonal IgG1 antibody which inhibits leukocyte vascular adhesion and migration into the gastrointestinal tract through α4β7 integrin blockade. Aims: We retrospectively assessed the 12-month, real-world efficacy and safety of VDZ as induction and maintenance therapy in adult patients with ulcerative colitis (UC). Methods: The rates of clinical remission (CR, partial Mayo score < 2), steroid-free clinical remission (SFCR), and mucosal healing were assessed with nonresponder imputation analysis. Baseline independent predictors of clinical remission were investigated, and adverse events were recorded. Results: We analyzed outcomes in 74 patients; 32% were anti-TNF naïve, 68% had pancolitis, and 46% were on systemic steroids at baseline. At week six, week 14, six months and one year, the CR rates were 26%, 34%, 39% and 39% respectively, and the SFCR rates were 24%, 31%, 38% and 39%, respectively. Among patients not in CR after induction, the probability of remission at six months was 20%. Sustained SFCR between weeks 14 and 52 and between weeks 22 and 52 was found in 69% and 86% of the patients, respectively. Steroid-free clinical remission at 12 months was significantly associated with remission after the induction phase (OR = 30.4; 95% CI, 6 to 150; P < 0.001). Mucosal healing rate at one year was 39%. The most common side effect was headache (7%). Conclusions: Increasing remission rates were observed over the first six months of VDZ treatment. One-fifth of patients not in remission post-induction achieved remission by six months of continued therapy. Mucosal healing was associated with higher rates of one-year steroid-free remission and VDZ treatment continuation.